Tissue specificity, localization in brain, and cell-free translation of mRNA encoding the A3 isoform of Na+,K+-ATPase. - Schneider, J W (1988)
The isolation of multiple Na+,K+-ATPase cDNAs from rat brain has led to the discovery of a family of alpha-isoform genes. Using A1 (alpha), A2 (alpha+), and A3 (alpha III) Na+,K+-ATPase gene probes, we have analyzed the distribution of Na+,K+-ATPase mRNAs in adult and fetal rat tissues by RNA blot and hybridization histochemistry. A1 Na+,K+-ATPase mRNA was found ubiquitously among various tissues, with highest levels in transport epithelial and neural tissues. A2 mRNA was found in adult neural and muscle tissues, and A3 mRNA was found only in neural tissues and fetal heart muscle. Both A1 and A2 mRNAs were less abundant in fetal brain than in adult brain; in contrast, A3 mRNA was abundant at both stages. In situ mapping of brain areas that contain A3 mRNA suggests that this Na+,K+-ATPase isoenzyme is expressed predominantly by neural cells. Analysis of Na+,K+-ATPase proteins generated by cell-free translation of synthetic mRNAs suggests that the A3 protein has properties similar to A2 (alpha+).